Removal of Anisakis simplex allergens from infected fish during the washing step of surimi production. (4th December 2014) - Olivares, Fabiola; González‐Muñoz, Miguel; Carballeda‐Sangiao, Noelia; Rodríguez‐Mahillo, Ana; Careche, Mercedes; de las Heras, Cristina; Navas, Alfonso; Tejada, Margarita
Abstract BACKGOUND The washing operation of fish muscle is one of the key steps in the production of surimi. The aim of this study was to assess in parasitised minced fish the effect of the washing steps on the allergen removal of Anisakis simplex and on protein yield during surimi processing. Experimentally infected hake (Merluccius merluccius) (50 Anisakis simplex s.s L3 larvae per 100 g of muscle) underwent three successive washing steps with water, phosphate buffer (20 mmol L−1), sodium bicarbonate (60 mmol L−1), or sodium hypochlorite (0.27 mmol L−1) in the surimi processing (4 kg muscle, 1:4 w/v for each solution). Total protein concentration and A. simplex antigens and allergens were evaluated in each waste fraction. RESULTS The highest removal of Ani s 4 and A. simplex antigens was achieved by using phosphate buffer, together with a good protein yield in the raw surimi. Decrease of the concentration of allergens and antigens as a function of the washing steps rendered a linear trend (R2 = 0.95 and 0.98 for Ani s 4 and A. simplex antigens, respectively). CONCLUSION The conditions for an optimal removal of Anisakis allergens can be established and calculated as a function of the washing steps. This approach opens a line to utilise parasitised fish in a safer way. © 2014 Society of Chemical Industry